Relationship-driven, family-centered care via TelePT: Reflections in the wake of COVID-19 - Choong, Elena America; Schladen, Manon Maitland; Alles, Yvonne Beth (Frontiers in Psychology, 2022)
In response to the throttling of children’s therapy programs precipitated by COVID-19 shutdowns, interest in the use of telehealth has increased among service providers at both the clinical and administrative levels. TelePT promises to be particularly appropriate in devising programs of on-going, therapeutic exercise interventions for children with neuromotor disorders. From the lay perspective, physical/physio-therapy (PT) which is seemingly characterized by the "hands-on," and corrective approach to managing impairments, makes a counter-intuitive candidate for delivery over telehealth. Over the past decades, however, PT as a discipline has increasingly adhered to a relationship-driven, family-centered model of intervention. This model is "hands-off," figuratively if not always literally and hence is not necessarily disconsonant with delivery mediated by telehealth technology. The current study explores in depth the experiences and reflections of seven practicing therapists, on the impact of telehealth, TelePT on the operationalization of relationship-based, family-centered methods into therapy. Interpretative Phenomenological Analysis was selected as the analytic method for understanding participants’ experience providing services using both distance and standard face-to-face practice modalities. Eight principal themes emerged from participants’ descriptions of their experience of delivering therapy over TelePT. Four of these themes correspond to the tenets of relationship-driven, family-centered care identified across four frameworks applied to pediatric rehabilitation. The remaining four themes focus on the particularities of the TelePT modality and its viability in clinical practice. The ability TelePT afforded to “see into the child’s environment,” emerged arguably as the greatest value of the modality in patient care. It revealed to therapists so much that they didn’t know about their patients’ progress and, more strikingly, had not realized they didn’t know. TelePT provides a unique window into the child’s functioning in the hours he is not in therapy. Given its potential in parent-therapist relationship building, assuring the ecological validity of therapy programs and the empowerment of families who seek it, TelePT is likely to be part of the future of PT and one driver of its evolution as a profession. There is a compelling case to retain TelePT modalities offering them alongside in-person formats for convenience, safety, and service quality enhancement.